Surgical oncological emergencies in octogenarian patients - Friziero, Alberto; Sperti, Cosimo; Riccio, Federica; Zuin, Irene Sole; Vallese, Lorenzo; Serafini, Simone; Amico, Alessandra; Valli, Valeria; Da Re, Chiara; Baldan, Nicola; Valmasoni, Michele; Da Dalt, Gianfranco (Frontiers in Oncology, 2023)
Background: Surgical Oncological emergencies represent a frequent challenge in acute settings, with post-operative courses characterized by high morbidity and mortality. An accurate selection of patients who could benefit from surgery is essential to avoid unnecessary invasive treatment. In this study we tried to determine if advanced age (> 80 years) represents a risk factor for negative shortterm outcome in patients undergoing emergency surgery for acute abdominal oncological illness.We retrospectively analyzed the records of patients who underwent emergency oncological surgery at the Department of Acute Care Surgery of Padua General Hospital from January t 2018 to December 2022. One-hundred and two cancer patients were included in the study: among them, 42 aged > 80 years (41%). Multiple preoperative and postoperative parameters were recorded and the follow-up period was at least 90 days. Multivariate logistic regression analyses were used to identify factors associated with short term post-operative outcomes. This is a provisional file, not the final typeset article Results: In octogenarians group, 30 days mortality was 11% vs 9.5% in younger group ( p = ns) and 90 days mortality was 17.6% in octogenarian group vs 20.5% in younger group ( p = ns). Postoperative morbidity and hospital length of stay were not significantly different in the two groups.Low albumin levels (OR 30.6,) and elevated LDH levels (OR 26.4, were predictive for short term mortality in surgical oncological emergencies.Conclusions: Advanced age is not a risk factor for negative outcomes in surgical oncological emergencies. Therefore, surgical options should be considered in octogenarians with oncological emergencies and acceptable clinical conditions. Serum Albumin levels and LDH can help to predict the postoperative outcome after surgery for oncological emergencies.